2020
DOI: 10.1177/1054773820907805
|View full text |Cite
|
Sign up to set email alerts
|

Bedrails and Falls in Nursing Homes: A Systematic Review

Abstract: Bedrail use for fall prevention in elderly clients (>65 years) is controversial. Some healthcare providers believe bedrails prevent falls, while others think they are ineffective and dangerous. A systematic review was conducted to address: “For older adults living in nursing homes, does more or less bedrail use reduce the incidence of falls?” We searched HealthStar, MEDLINE, CINAHL, Academic Search complete ProQuest and Canadian Health Research Collection using “elder*,” “bedrail*,” “fall*,” and “assisted-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…These strategies, however, produced opposite effects to nurses’ intention and resulted in patients walking to a room toilet or climbing over bedrails, which increased the risks of falling and injury. This is consistent with the results of a systematic review, which suggested that the use of bedrails could not prevent falls but increased patient injuries [ 44 ]. Trying to prevent falls, while facing multiple competing tasks with frequent interruptions, can cause a target fixation that narrows down nurses’ attention and prevents them from seeing the big picture of the situation [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…These strategies, however, produced opposite effects to nurses’ intention and resulted in patients walking to a room toilet or climbing over bedrails, which increased the risks of falling and injury. This is consistent with the results of a systematic review, which suggested that the use of bedrails could not prevent falls but increased patient injuries [ 44 ]. Trying to prevent falls, while facing multiple competing tasks with frequent interruptions, can cause a target fixation that narrows down nurses’ attention and prevents them from seeing the big picture of the situation [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Reasons that have triggered the use of ‘supportive devices’ were sustaining posture, promoting comfort, and enabling mobilisation, as well as answering the need of patients who feel themselves more protected. These reasons have never been documented before, with the exception of bed rails [ 27 , 42 ]. Thus, the findings suggest that some physical devices can have an extended role, not only to limit freedom, but also to potentiate the residual abilities and to promote independence.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, despite a considerable amount of literature [ 3 ], controversial considerations are still present regarding some physical restraints. For example, bed rails [ 27 ] have been defined as ‘moderate restrictive measures’ in some cases [ 28 ], thus underlining that restraints are not homogeneous, even when involving the same ethical principles.…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 meta-analysis reviewing bed rail use in LTC homes concluded that there is insufficient evidence to suggest the use of full bed rails as a falls prevention strategy. ( 50 ) There is a body of research that shows physical restraints are associated with death, ( 8 ) increased risk of injuries, faster cognitive decline, lower ADL performance, physical decline, increased incontinence, and pressure wounds. ( 39 ) In the context of the quality of life and health of an older adult in LTC, research evidence and best practice guidelines support the minimization and/or reduction of restraint use.…”
Section: Discussionmentioning
confidence: 99%